The Gibraltar Issue: A Framing and Discourse Analysis of Spain During the Brexit Negotiation - Rahmadan, Yanuar (Universitas Cenderawasih, 2024)
Gibraltar becomes one of the issues that emerged during the Brexit negotiation in the British withdrawal from the European Union. Spain becomes the inseparable actor in discussing the issue due to its long-standing interference in Gibraltar. Spain used the long process of Brexit to provoke and predispose Gibraltar to its advantages. This study aims to explore the framing of Spain’s role in the context of Brexit negotiations concerning Gibraltar by analysing a selection of British and French news articles. A discourse-historical analysis is also used by analysing speeches delivered by the Chief Minister of Gibraltar. From the framing and discourse-historical analysis, this study found that Spain has become the inseparable actor and has been framed in negative terms concerning the Gibraltar issue. Spain appears consistently in the corpus that is used in this study and is mentioned to attempt bringing back Gibraltar as a Spanish territory. The Chief Minister of Gibraltar also referred to Spain as a threat and treated Spain as the aggressor. In addition, this study adopts a constructivist perspective to bring insights into the sentiments behind the framing and discourses that emerged during the Brexit negotiations, especially on the involvement of Spain in discussing the Gibraltar issue. KEYWORDSBrexit Negotiation; Constructivist Approach; Gibraltar; Spain